Perbandingan Latihan Hollow Sprint Dan Repetition Dalam Pembelajaran Atletik Terhadap Kecepatan Lari Sprint 100 Meter Siswa Menengah Atas - Muhamad Hanafi; Febi Kurniawan; Abdul Salam Hidayat (Jurnal Ilmiah Wahana Pendidikan, 2023)
Muhamad Hanafi Comparison of Hollow Sprint and Repetition Exercises in Athletics Learning on the 100 Meter Sprint Speed of High School Students. The background of the problem in making this thesis is an inappropriate method so that it will hinder the delivery of material to students. Thus, it is necessary to pay attention to the mastery of the material, the mastery of the material, the management of students and the selection of appropriate learning methods so that a learning takes place properly and effectively. Is there a significant effect between Hollow Sprint training and Repitition Training 100 meter sprint running on students at SMA Negeri 1 Cikarang Utara. To answer the formulation of the research problem that has been formulated, the author uses a quantitative approach method. The population in this study were students of class X SMA Negeri 1 Cikarang Utara, Cikarang which opened 20 students. The sample used, according to Arikunto (2006:107) is just a precursor, so if the subject is less than 100, it is better to take all the researchers who are population studies. If the number of subjects is large it can be taken 10-15% or 20-25% or more. In accordance with the title of the study, the research design used was posttest-only control design, namely an experimental design consisting of two groups, with the first group being treated as an experimental group and the second group being treated as a group. (Sugiyono, 2003:85). Sampling in this researcher uses a random sampling technique, that is, it is done by taking the subject at random. Because the number of samples was 360, the researchers set a sample size of 20% of 360 students, namely 60 students who were divided into two groups, namely 30 groups who received sprint training using the hollow sprint method and 30 groups who received sprint training using the sprint method. repetition practice